Pythium insidiosum: desenvolvimento de modelo experimental de infecção em ovos embrionados de Gallus gallus domesticus - Verdi, Camila Marina (2017)
The pythiosis is a severe disease caused by the oomycete Pythium insidiosum that affects animals and humans. If not diagnosed and treated quickly, the pythiosis can lead to death of the affected individual. Treatment of pythiosis is difficult, as it does not respond well to drugs commonly used in fungal diseases, due to the absence of ergosterol in the P. insidiosum membrane. Currently, research on pythiosis treatment uses the rabbit as a model of experimental infection, since they develop an infection similar to that of equines. Seeking to rationalize the use of animals in scientific experimentation, alternative models and in vitro models are increasingly indispensable options. In this context, the use of embryonated chicken eggs (Gallus gallus domesticus), in researches with viruses, bacteria and fungi, has been shown to be easy to handle, low cost and good reproducibility, as well as aid in studies of pathogenesis and discovery of new treatments. In this scenario, this work had the objective of developing a new model of experimental infection in vivo for pythiosis, as well as test new treatments. Initially, tests were done to standardize the day of infection and inoculum concentration. After this process, toxicity tests were performed with azithromycin, itraconazole and terbinafine, which had already shown action against P. insidiosum in vitro. The concentrations used for azithromycin were 0.2 μg/egg, 1.6 μg/egg and 12.8 μg/egg, itraconazole 12.8 μg/egg and terbinafine 12.8 μg/egg, being administered 0.025 ml in three time intervals, 8/8 hours, 12/12 hours or 24/24 hours. The results showed that the best day for induction of infection was on the 14th day of embryonic development, using a concentration of 500 zoospores/mL, infecting 95% of embryos inoculated, affecting mainly the blood vessels. Itraconazole and terbinafine were toxic at concentration tested, regardless of the time intervals in which the doses were administered, on the other hand, azithromycin has not been shown to be toxic at any dose or interval of administration. From this study, we propose a new experimental model of pythiosis using embryonated chicken eggs. This model can assist in efficacy trials of new treatments quickly and easily.